Analisis Vegetasi Tumbuhan Tingkat Pohon di Kawasan Geopark Silokek Kabupaten Sijunjung - Pertiwi, Vera; Chairul, Chairul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Silokek Geopark Area is a geopark area that is being appointed into a national geopark consisting of 25 geodiversity, 12 biodiversity, and 17 cultural diversity sites. The objective of the study is to determine the composition and structure of vegetation of trees in the Silokek Geopark area, Sijunjung Regency. This research has been conducted from September to December 2022 by using the transect method. The plot was made of 10 plots with a size of 10x10 meters for vegetation that is placed alternately on both sides of the transect. Identification is carried out at the Andalas University Herbarium. Based on the research results, 15 families, 19 genera, 22 species, and 30 individuals were found. The co-dominant families are Moraceae (20%), Ebenaceae (16.67%), and Euphorbiaceae (13.33%). The highest important value index of Ficus Stricta was obtained at 57.86% and the lowest in the Nephelium Lappaceum at 7.36%. The plant diversity index in this area is classified as moderate (H '= 2.85). It is recommended that the government to controlling the diversity of plants in the Silokek Geopark area, considering that this area is a tourist area.